Do behavioural biases impact corporate entrepreneurship, agency cost and firm performance: Evidence from developed and developing economies? - Nousheen Tariq Bhutta; Syed Zulfiqar Ali Shah (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
The study aims to extend the relationship of corporate entrepreneurship and agency cost to firm performance, in the presence of behavioral biases to address the behavioral finance approach and validate it in developed (USA) and developing (Pakistan) economies, in order to generalize the study. Behavioral biases might be different across economies, particularly infers the diverse cultures. The validated construct has been adopted to measure the corporate entrepreneurship, behavioral biases and risk perception of USA and Pakistani non-financial sector companies listed on the New York Stock Exchange (NYSE) and the Karachi Stock Exchange (KSE), respectively. The data for firm performance and agency cost has been taken from Balance Sheets Analyses (SBP Report) for Pakistani companies and from annual reports of the USA companies on three yearly average bases (2009, 2010 and 2011). Data has been collected from 257 USA companies and 175 Pakistani Companies listed at NYSE and KSE respectively. The finding shows that behavioral biases don't impact the entrepreneurial orientation. The executives perform entrepreneurial activities differently, varies from individual to individual.
Keywords: 330